2022
DOI: 10.3389/fimmu.2022.913667
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Prognostic Factors in Patients With Antineutrophil Cytoplasmic Antibody-Associated Vasculitis: A 15-Year Multicenter Retrospective Study

Abstract: BackgroundAntineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) is a multisystem autoimmune disease with small-vessel involvement. In AAV, microscopic polyangiitis (MPA) and granulomatosis with polyangiitis (GPA) are major clinicopathologic variants. In addition, myeloperoxidase (MPO) and proteinase 3 (PR3) are major target antigens. The objective of the study was to explore the predictive factors for long-term survival in AAV patients.Materials and MethodsA multicenter retrospective study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 38 publications
2
5
1
Order By: Relevance
“…In fact, liver involvement was proven to be related to the disease activity and to predict poor clinical outcomes. 9 In the present case, the patient did not comply with the treatment. He presented after two years with acute heart failure with a rapidly progressive fatal outcome.…”
Section: Discussioncontrasting
confidence: 50%
“…In fact, liver involvement was proven to be related to the disease activity and to predict poor clinical outcomes. 9 In the present case, the patient did not comply with the treatment. He presented after two years with acute heart failure with a rapidly progressive fatal outcome.…”
Section: Discussioncontrasting
confidence: 50%
“…A calibration curve and decision curve analysis (DCA) were used to evaluate the clinical applicability of the nomogram. 17 The calibration curve was plotted through bootstrap sampling 2000 times, and it showed that the predicted values by the nomogram were in line with the actually observed values (Fig. 3A).…”
Section: Establishment and Validation Of A Predictive Modelsupporting
confidence: 59%
“…Decision curve analysis (DCA) was performed to assess the clinical applicability of the nomogram as we previously described. 30 The nomogram with MLR and ELR added high net benefits within a wide range of threshold probabilities ( Figure 8B ). Calibration curves were plotted through bootstrap sampling 2000 times.…”
Section: Resultsmentioning
confidence: 94%